Asuhan Kebidanan Berkelanjutan Ny. ”N’ Di Rumah Sakit Khusus Daerah Ibu Dan Anak Siti Fatimah Makassar Tahun 2023 - Hafsah Hafsah (Jurnal Ventilator, 2024)
Comprehensive midwifery care is a complete examination provided with simple examinations and counseling for pregnancy, childbirth, postpartum, and newborn care. The goal of continuous midwifery care given to Mrs. "N" at the Special Hospital for Mother and Child Siti Fatimah is to assess the condition of the mother and her fetus. This study was conducted from April 14, 2023, to July 9, 2023. Midwifery care methods use midwifery management based on the 7 steps of Verney from 38 weeks of pregnancy until deciding to use a 3-month contraceptive injection. The results of prenatal care include two antenatal visits during pregnancy. In the third trimester, Mrs. "N" complained of back pain, which was already manageable by the mother, so throughout the pregnancy, Mrs. "N" remained in good and normal condition. In conclusion, Mrs. "N" gave birth normally, assisted by a midwife and following the established care plan. The baby was born spontaneously with the head presenting, female, birth weight: 2,900 grams, birth length: 46 cm. Postpartum care for Mrs. "N" proceeded smoothly, and there were no complications for both the mother and the baby. The midwife provided communication, information, and education (CIE) during the care process, and during the postpartum period, the mother decided to use a 3-month contraceptive injection after 42 days of the postpartum period.